2013
DOI: 10.1007/s11284-012-1022-9
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic matter dynamics: a biological perspective derived from the use of compound‐specific isotopes studies

Abstract: Current attempts to explain the persistence of carbon in soils focuses on explanations such as the recalcitrant plant residues and the physical isolation of substrates from decomposers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
147
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(159 citation statements)
references
References 86 publications
4
147
1
4
Order By: Relevance
“…Comparing the maps for each element, before and after application, there were a few similarities in the patterns of spatial distribution, indicating that the incorporation of neem cake must have influenced the dynamics of these nutrients in the treated area. The increase in the variability of C-CO 2 evolution rate due to neem cake incorporation possibly results from the influence of the organic matter on the different microbial communities (Gleixner, 2013). For OC (Figures 1F-C1, 1F-C2 and 1F-C3), neem cake application increased the variability and the contents in the soil, showing narrower lines at the end of the study.…”
Section: Resultsmentioning
confidence: 91%
“…Comparing the maps for each element, before and after application, there were a few similarities in the patterns of spatial distribution, indicating that the incorporation of neem cake must have influenced the dynamics of these nutrients in the treated area. The increase in the variability of C-CO 2 evolution rate due to neem cake incorporation possibly results from the influence of the organic matter on the different microbial communities (Gleixner, 2013). For OC (Figures 1F-C1, 1F-C2 and 1F-C3), neem cake application increased the variability and the contents in the soil, showing narrower lines at the end of the study.…”
Section: Resultsmentioning
confidence: 91%
“…SOM models that include microbial community structure have shown that changes in microbial physiology, often expressed as CUE (defined as the amount of C in microbial biomass relative to C respired and in biomass), have the potential to dramatically impact the fate of C stocks to climate change (Allison et al, 2010;Schimel, 2013;Wieder et al, 2013;Li et al, 2014), and experimental evidence shows that CUE can be altered by substrate quality, temperature, and N availability (Dijkstra et al, 2011;Manzoni et al, 2012;Frey et al, 2013;Tucker et al, 2013). This concept of changes to CUE is of particular importance as a large portion of SOM has been attributed to microbial derived products, which may have a relatively long turnover time (Simpson et al, 2007;Liang and Balser, 2008;Miltner et al, 2012;Gleixner, 2013). It is therefore necessary to determine the underlying mechanisms and the extent that microbial community structure and function impacts C turnover in response to these global change scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in soil science have shown that (1) SOM degradation is rather controlled by physical protection and accessibility of soil microorganisms to SOM rather than the chemical composition, or recalcitrance, of soil organic molecules (Dungait et al 2012;Schmidt et al 2011) and (2) that SOM decomposition leads to a progressive evolution of SOM chemistry toward a more microbial character due to the incorporation of microbial metabolites and microbially reworked plant-derived compounds in the residual SOM (Gleixner 2013;Hobara et al 2014;Malik and Gleixner 2013). Several agricultural practices can potentially affect one of these two features or both.…”
Section: Discussionmentioning
confidence: 99%
“…Several soil management practices such as tillage or organic fertilizer application are known to stimulate the microbial decomposition of SOM (Luo et al 2010;McLauchlan 2006;Pisani et al 2016). Beyond their role as decomposers, microorganisms are a ubiquitous source of OM to soils through recycling of plant and animal-derived OM and synthesis of new products (Dungait et al 2012;Gleixner 2013;Miltner et al 2012). Consequently, SOM decomposition leads to an enrichment in microbial compounds in residual SOM at the expense of plant-derived compounds (Hobara et al 2014;Kaiser and Kalbitz 2012;Malik and Gleixner 2013).…”
Section: Introductionmentioning
confidence: 99%